Development of the tourism destination brand «GREAT Britain» - Kairova, A. A. (Journal of Economic Research & Business Administration, 2016)
In this paper, the author analyzes the foreign experience of development of tourism brand of UK. Despite the fact that the UK has a strong and positive brand in the world community, there are problems in the perception of the country as the best tourism destination. Deteriorating situation the circumstances prevailing in the country (lack of competitiveness of the country’s image and the range of tourism products, travel restrictions, reduction of public funding, etc.) and complex competitive sphere on world tourism market, which worsens developed country as in developing markets in China, Turkey and Macao too. In order to strengthening world positions and entry in five best tourism countries world till 2020 government of Great Britain develops new policy in areas of tourism development, approves strategy growth of entrance tourism and actively introduces marketing campaign aimed at the promotion and strengthening of the country’s image on external and internal markets under the brand «Great Britain».